Isolation of Vibrio cholerae from sewerage and awareness level regarding Cholera among the residents of Lahore - Ghazanfar, Jawaria; Sarwar, Huda; Abbas, Zainab; Salamat Ali, Jawad; Razzaq, Anjum; Mazhar, Iqra Jabeen; Khawaja, Shifa (International Journal of Research in Medical Sciences, 2024)
Background: Cholera is a major public health concern which is caused by Vibrio cholerae, found in freshwater, sewage and clinical reservoirs. The Water and Sanitation Agency (WASA) maintains water supply and sewerage services in Lahore, Pakistan. This study aimed to isolate V. cholera from sewage managed by WASA and to evaluate the awareness and sociodemographic factors linked to V. cholerae isolation and cholera awareness in Lahore residents. Methods: A cross-sectional study was conducted on 100 sewerage sample from 8 towns of Lahore to isolate V. cholera. 300 individuals each representing 01 household were interviewed to assess the level of knowledge, attitude and practice regarding cholera. Sewerage samples were analyzed using the TCBS agar and Oxidase test. The serotype of positive samples was found using antisera. Results: V. cholera (serotype O1) was isolated from 2 out of 100 sewerage samples from 2 out of 8 towns of Lahore. In areas where V. cholera was detected the average score of knowledge, attitude and practice among the residents was less as compared to the areas where it was not detected. The history of acute watery diarrhea among household was statistically significant in areas where V. cholera was detected (p value 0.044). Conclusion: The isolation and the detection of V. cholera serotype O1 signifies the fact that V. cholera is present in Lahore. The residents of the area where V. cholera was detected had low level of knowledge, attitude and practice as compared to the areas where it was not detected.